Managing Prolactinomas during Pregnancy - Almalki, Mussa Hussain; Alzahrani, Saad; Alshahrani, Fahad; Alsherbeni, Safia; Almoharib, Ohoud; Aljohani, Naji; Almagamsi, Abdurahman (Frontiers in Endocrinology, 2015)
Prolactinomas are the most prevalent functional benign pituitary tumors due to a pituitary micro- or macroadenoma. The majority of patients presents with infertility and gonadal dysfunction. A dopamine agonist (DAs) (bromocriptine or cabergoline) is the treatment of choice that can normalize prolactin levels, reduce tumor size and restore ovulation and fertility. Cabergoline generally preferred over bromocriptine because of its higher efficacy and tolerability. Managing prolactinomas during pregnancy may be challenging. During pregnancy, the pituitary gland undergoes global hyperplasia due to a progressive increase in serum estrogens level that may lead to increase of the tumor volume with potential mass effect and visual loss. The risk of tumor enlargement may occur in 3 % of those with microadenomas, 32 % in those with macroadenomas that were not previously operated on and 4.8% of those with macroadenomas with prior ablative treatment. Though both drugs appear to be safe during pregnancy, the data on fetal exposure to DAs during pregnancy have been reported with bromocriptine far exceeds that of cabergoline with no association of increased risk of pregnancy loss and premature delivery. It is advisable to stop the use of DAs immediately once pregnancy is confirmed, except in the case of women with invasive macroprolactinomas or pressure symptoms. This review outlines the therapeutic approach to, prolactinoma during pregnancy, with emphasis on the safety of available DA therapy.